Pengaruh Brand Loyalty, Word Of Mouth, Dan Celebrity Endorsement Terhadap Repurchase Intention - Ferdinands, Leonardo Charles (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Repurchase intention is something that must be noticed by companies that provide products or services. Due to the repurchase intention of a customer, the sales level of a product or service will continue and the company will get its sales again. The purpose of this study was to determine the effect of brand loyalty, word of mouth and celebrity endorsement on repurchase intention, one of the sports product brands. The research method that been used in this study is multiple linear regression and data collection techniques used are using questionnaires distributed online through help from Google Form. The population and sample in this study were all people who knew and had bought a product from one of the sports brands, and the total number of respondents collected was 150 people. The results of this study are that brand loyalty, word of mouth and celebrity endorsement have a positive influence on repurchase intention.